2019
DOI: 10.5603/gp.2019.0057
|View full text |Cite
|
Sign up to set email alerts
|

Lower uterine segment involvement in lymphovascular space invasion and lymph node metastasis in endometrioid endometrial cancer

Abstract: Objectives: To evaluate the correlation between lymphovascular space invasion (LVSI) indicating lower uterine segment involvement (LUSI) in endometrioid endometrial cancer and lymph node metastasis based on the lymphatic drainage difference between the uterine corpus and the lower segment. Material and methods: Patients who underwent staging surgery for endometrioid endometrial cancer between January 2010 and January 2019 at our institution were reviewed. The clinicopathologic findings and LUSI status of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…11 There are conflicting results regarding the importance of LUS involvement in traditionally staged EC. 16,18,20 Although ULSI seems to be associated with worse survival outcomes, the main reason for increasing LN involvement in cases with ULSI is the possibility of high LVSI rates. 16,20,21 In the literature, ULSI rates in EC cases have been reported in a wide range of 3%-42%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 There are conflicting results regarding the importance of LUS involvement in traditionally staged EC. 16,18,20 Although ULSI seems to be associated with worse survival outcomes, the main reason for increasing LN involvement in cases with ULSI is the possibility of high LVSI rates. 16,20,21 In the literature, ULSI rates in EC cases have been reported in a wide range of 3%-42%.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] There are few studies in the literature with conflicting results examining the effect of ULSI on endometrial cancer prognosis. [16][17][18][19] Our aim in this study is to investigate the effect of ULSI on prognosis in early-stage (stage I) EC cases diagnosed and treated in our clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of the cervix or lower uterine segment in endometrial carcinoma is associated with adverse prognostic factors, such as myometrial infiltration, serous surface of the uterus involvement, lymph node metastasis, and higher histological grade [ 38 ]. Cokmez et al found that lower uterine involvement and lymphovascular space invasion were significantly correlated with lymph node metastasis [ 39 ]. Kizer et al also showed that lower uterine segment involvement was associated with a high risk of recurrence and death in patients with early EC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cokmez and Yilmaz reported LUSI in 49 (19.4%) of 253 cases of endometrioid endometrial carcinoma [32]. Patients with LUSI presented more LVSI (36.7% vs. 11.8%, p < 0.05) and more lymph node metastasis (18.4% vs. 4.9%, p < 0.05) than patients without LUSI [32]. Pathologists should report LUSI because this information could be used as a staging criterion for endometrial carcinoma in the future.…”
Section: Plos Onementioning
confidence: 98%
“…Lower uterine segment involvement (LUSI) correlates with more LVSI and other poor prognostic factors, such as lymph node metastasis, uterine serosal involvement, and deep myometrial invasion [31]. Cokmez and Yilmaz reported LUSI in 49 (19.4%) of 253 cases of endometrioid endometrial carcinoma [32]. Patients with LUSI presented more LVSI (36.7% vs. 11.8%, p < 0.05) and more lymph node metastasis (18.4% vs. 4.9%, p < 0.05) than patients without LUSI [32].…”
Section: Plos Onementioning
confidence: 99%